Women's circles as a culturally safe psychosocial intervention in Guatemalan indigenous communities: a community-led pilot randomised trial - Anne Marie Chomat; Aura Isabel Menchú; Neil Andersson; Manuel Ramirez-Zea; Duncan Pedersen; Alexandra Bleile; Paola Letona; Ricardo Araya (BMC, 2019)
Abstract Background Indigenous Maya women in Guatemala show some of the worst maternal health indicators worldwide. Our objective was to test acceptability, feasibility and impact of a co-designed group psychosocial intervention (Women's Circles) in a population with significant need but no access to mental health services. Methods A parallel group pilot randomised study was undertaken in five rural Mam and three periurban K'iche' communities. Participants included 84 women (12 per community, in seven of the communities) randomly allocated to intervention and 71 to control groups; all were pregnant and/or within 2 years postpartum. The intervention consisted of 10 sessions co-designed with and facilitated by 16 circle leaders. Main outcome measures were: maternal psychosocial distress (HSCL-25), wellbeing (MHC-SF), self-efficacy and engagement in early infant stimulation activities. In-depth interviews also assessed acceptability and feasibility. Results The intervention proved feasible and well accepted by circle leaders and participating women. 1-month post-intervention, wellbeing scores (p-value 0.008) and self-care self-efficacy (0.049) scores were higher among intervention compared to control women. Those women who attended more sessions had higher wellbeing (0.007), self-care and infant-care self-efficacy (0.014 and 0.043, respectively), and early infant stimulation (0.019) scores. Conclusions The pilot demonstrated acceptability, feasibility and potential efficacy to justify a future definitive randomised controlled trial. Co-designed women's groups provide a safe space where indigenous women can collectively improve their functioning and wellbeing. Trial registration ISRCTN13964819. Registered 26 June 2018, retrospectively registered.